COSMIC RAY- AND GAS RETENTION AGES OF NEWLY RECOVERED AND OF UNUSUAL CHONDRITES - Eugster O.; Polnau E.; Terribilini D. (My University, 1998)
We report the isotopic abundances of He, Ne, and Ar of four chondrites that fell in China, Jiange (H5), Juancheng (H5), Yanzhuang (H6), and Bo Xian (LL4), of Kagarlyk (L6) fallen in Russia, of Kress (L6) and Hunter (LL6) found in the USA, and of two Antarctic chondrites, Y-73001 (H4–6) and Y-73004 (L5–6). The most important data that have direct consequences for the study of meteorite delivery dynamics to Earth crossing orbits are the cosmic ray exposure ages. They provide the constraints on meteorite origin, orbital evolution, and regolith dynamics of the meteorite parent bodies. Dynamical studies show how meteorites can reach Earth within a few million years. This time-scale can be checked against the cosmic ray exposure age determined from laboratory studies of the nuclides accumulated as a result of their exposure to high energy particles. For Jiange, Juanchen, Yanzhuang, and Bo Xian we obtain cosmic ray exposure ages of 6.0, 5.3, 2.14, and 37.3 Ma, respectively. Yanzhuang yields extremely low 4He and 40Ar gas retention ages and we conclude that this material experienced a thermal event at or before break-up of its parent body. Kagarlyk fell within five hours after the Tunguska event in 1908 but we find that this meteorite is not related with the Tunguska bolide. Kress yields an exposure age of 32 Ma whereas Hunter with 0.5 Ma shows the shortest exposure age for any LL chondrite dated until now. The two Antarctic finds, Y-73001 and Y-73004 yield exposure ages of 16.1 Ma and 23.2 Ma, respectively.